Self-sensing morphing wing using shape memory alloy actuator - Azid, Nuramirah; Abdullah, Ermira Junita; Harmin, Mohammad Yazdi (The Aeronautical and Astronautical Society of the Republic of China, 2025)
The aerodynamic efficiency of wing can be improved by using morphing wing system actuated by smart material. Shape memory alloy (SMA) can be used in such system to replace conventional actuator in order to reduce the weight of the wing. SMA acts as an actuator, embedded inside the wing to achieve the desired camber profile during flight. This study explores the self-sensing capability of the SMA by changing the resistivity during actuation using voltage drop across the SMA as the input to the feedback system. The self-sensing system can reduce the weight and cost as sensors can be eliminated. The SMA actuator was controlled using Proportional-Integral-Derivative (PID) controller with LabVIEW software where the voltage drop across the SMA acts as input to control the shape of the wing. The calibration data was critical to design the morphing wing actuation for the wind tunnel testing. The data was also analyzed to determine the voltage required to change the geometry of the morphing wing and improve the aerodynamics behavior in terms of lift-to-drag (L/D) ratio. The wing model was tested at angle of attack between -12° and 16° at wind speed of 20m/s. The experimental results of wind tunnel testing showed that the morphing wing system produced improvement on lift, drag and lift-to-drag ratio as predicted from earlier work using computational fluid dynamics. L/D improved as much as 9.2 at 4° AOA for SMA actuation of 3.5V and 10.79 at at 6° AOA for SMA actuation of 4.8V.